Influence of a low‐dose supplementation of curcumagalactomannoside complex (CurQfen) in knee osteoarthritis: A randomized, open‐labeled, active‐controlled clinical trial. (18th November 2020) - Thomas, Jestin V.; Smina, Thozhuthum Parambil; Khanna, Aman; Kunnumakkara, Ajaikumar B.; Maliakel, Balu; Mohanan, Ratheesh; Krishnakumar, Illathu Madhavamenon
Abstract : A 6‐week, randomized, open‐label, active‐controlled clinical trial was conducted to evaluate the influence of a low‐dose curcumagalactomannosides (CGM) (400 mg once daily) in OA subjects. The treatment was compared with a standard combination of 500 mg glucosamine hydrochloride (GLN) and 415 mg chondroitin sulphate (CHN), supplied as a single oral dose twice a day. Out of 84 subjects randomized, 72 subjects who have completed the study were evaluated for the safety and efficacy of the treatments at baseline and subsequent visits (day 28 and 42), by measuring walking performance, VAS, KPS, and WOMAC scores. CGM exhibited 47.02, 21.43, and 206% improvement in VAS, KPS, and walking performance, respectively, compared to the baseline. Similarly, there was 31.17, 32.93, 36.44, and 35% improvement in the pain, stiffness, physical function, and total WOMAC scores. CGM also caused a substantial reduction in the serum inflammatory marker levels. The results indicate that a short‐term supplementation of a low dosage CGM exerted superior beneficial effects than a high‐dosage CHN–GLN combination in alleviating the pain and symptoms of OA subjects. Further clinical trials of extended duration in a larger population is required to substantiate the efficacy of CGM in the long‐term management of OA.